2018
DOI: 10.1183/13993003.00278-2018
|View full text |Cite
|
Sign up to set email alerts
|

Electronic cigarette use in youths: a position statement of the Forum of International Respiratory Societies

Abstract: Children and adolescents are highly susceptible to nicotine addiction, which affects their brain development, even in those who smoke infrequently. Young people who become addicted to nicotine are at greater risk of becoming lifelong tobacco consumers. The use of nicotine-delivering electronic cigarettes has risen dramatically among youths worldwide. In addition to physical dependence, adolescents are susceptible to social and environmental influences to use electronic cigarettes. The product design, flavours,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
78
0
6

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 111 publications
(104 citation statements)
references
References 84 publications
3
78
0
6
Order By: Relevance
“…Compared to the research findings of other previous studies, we found that pregnant women exposed to FHS and SHS have a similar, and sometimes even much lower HRQoL than those suffered from physiological diseases, such as gestational diabetes mellitus and uterine fibroid. [29,50] Although electronic cigarettes has been considered as a safer way than smoking tobacco among people recent years, [51] recent studies have stated that e-cigarette products still can cause varying degree of lung damage and chronic respiratory symptoms and both DNA strand breaks and cell death; [52][53][54] Thus, the…”
Section: Discussionmentioning
confidence: 99%
“…Compared to the research findings of other previous studies, we found that pregnant women exposed to FHS and SHS have a similar, and sometimes even much lower HRQoL than those suffered from physiological diseases, such as gestational diabetes mellitus and uterine fibroid. [29,50] Although electronic cigarettes has been considered as a safer way than smoking tobacco among people recent years, [51] recent studies have stated that e-cigarette products still can cause varying degree of lung damage and chronic respiratory symptoms and both DNA strand breaks and cell death; [52][53][54] Thus, the…”
Section: Discussionmentioning
confidence: 99%
“…A few of the younger children believed the fruits in flavourings made them healthier. Such findings are noteworthy given concerns about the attraction of flavoured e-cigarettes to young people and recent calls to prohibit them (18,26). Further research is needed to understand the potential appeal of flavoured e-cigarettes to youth and assess if further regulation is warranted.…”
Section: Acceptability Of Vaping and Smokingmentioning
confidence: 90%
“…In 2015/16 the Welsh government proposed to ban the use of e-cigarettes in enclosed public places in Wales; the proposal was rejected by the Welsh Assembly. In 2018 the Forum of International Respiratory Societies recommended a worldwide ban on the sale of e-cigarettes to young people, the prohibition of flavourings and use of e-cigarettes where children are present (18). Recently the U.S Food and Drug Administration (FDA) announced the implementation of new and aggressive measures including the re-examination of their compliance policy regarding flavoured e-cigarettes which could potentially see the removal of some or all flavoured products (26) .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As stated previously, observational data are subject to various biases and may establish an association but cannot prove a causal link. It may simply be that certain youth experiment with whatever is available; however, the evidence is sufficiently concerning that many authorities agree that ENDS advertising to youth should be banned, flavourings should be banned and ENDS use should be strictly controlled …”
Section: Ends May Lead To Smoking?mentioning
confidence: 99%